A mild, efficient and catalyst-free thermoreversible ligation system based on dithiooxalates. Issue 19 (22nd April 2016) - Pahnke, Kai; Haworth, Naomi L.; Brandt, Josef; Paulmann, Uwe; Richter, Christian; Schmidt, Friedrich G.; Lederer, Albena; Coote, Michelle L.; Barner-Kowollik, Christopher
Abstract : We introduce dithiooxalates as efficient and catalyst-free thermoreversible hetero Diels–Alder linkers for applications in self-healing materials, organic sheets, mild ligation or complex architecture design. Abstract : We demonstrate a novel and ready to prepare thermoreversible hetero Diels–Alder dilinker on the basis of dithiooxalates, enabling the mild, rapid and catalyst-free linkage of diverse diene species under ambient conditions for applications in the fields of, for example, modular ligation, self-healing or recyclable materials and surface modification amongst others. The linker was studied using quantum chemical calculations, and experimentally in small molecular reactions via UV/Vis spectroscopy, mass spectrometry and NMR as well as in step-growth polymerizations with diene-difunctional building blocks – characterized via (temperature dependent) SEC and HT NMR – as an example for efficient polymer ligation.